Absorption properties of high-latitude Norwegian coastal water: The impact of CDOM and particulate matter. (5th September 2016) - Nima, Ciren; Frette, Øyvind; Hamre, Børge; Erga, Svein Rune; Chen, Yi-Chun; Zhao, Lu; Sørensen, Kai; Norli, Marit; Stamnes, Knut; Stamnes, Jakob J.
Abstract: We present data from measurements and analyses of the spectral absorption due to colored dissolved organic matter (CDOM), total suspended matter (TSM), phytoplankton, and non-algal particles (NAP) in high-latitude northern Norwegian coastal water based on samples taken in spring, summer, and autumn. The Chlorophyll- a (Chl- a ) concentration was found to vary significantly with season, whereas regardless of season CDOM was found to be the dominant absorber for wavelengths shorter than 600 nm. The absorption spectral slope S 350−500 for CDOM varied between 0.011 and 0.022 nm −1 with mean value and standard deviation given by (0.015 ± 0.002) nm −1 . The absorption spectral slope was found to be strongly dependent on the wavelength interval used for fitting. On average, S 280−500 was found to be 43% higher than S 350−500 . A linear relationship was found between the base 10 logarithm of the absorption coefficient at 440 nm [log( a g (440))] and S 350−500 . Regardless of season, phytoplankton were the dominant component of the TSM absorption indicating little influence from land drainage. The mean values of the Chl- a specific absorption coefficient of phytoplankton a p h * ( λ ) at 440 nm and 676 nm were 0.052 m 2 mg −1 and 0.023 m 2 mg −1, respectively, and a p h * ( λ ) was found to vary with season, being higher in summer and autumn than in spring. The absorption spectral slope S NAP, which is the spectral slope of absorption spectrum for non-algal particles, was lower than that for European coastal water in general. It varied between 0.0048 and 0.022 nm −1 with mean value and standard deviation given by (0.0083 −1 ± 0.003) nm −1 . Comparisons of absorption coefficients measured in situ using an ac-9 instrument with those measured in the laboratory from water samples show a good agreement.